Technical Study and Financial Analysis of Red Tilapia Cultivation (Oreochromis niloticus) in Running Water System Using Different Feeds at PT Ikan Bangun Indonesia (IWAKE) Bogor, West Java - Raihan Maulana Firdaus; Mugi Mulyono; Mochammad Farchan (Airlangga University, 2020)
Red tilapia is one of the commodities that can be cultivated in the running water pond. With the technology of running water ponds that depend on feeding. The cost of feed in production ranges from 60-70% of the total cost. Therefore, innovation in feed is needed to reduce production costs. Then an experiment was carried out aimed at finding out the efficiency in feeding maggot and pellet feed in red tilapia in the running water pond system. Some experiments were carried out by giving full feed pellets and substitution in maggot feed 50%. This research was conducted 75 days from March 2, 2020 to May 15, 2020. Observed parameters were production technique from stocking to harvest, frequency and dose, feed conversion ratio, daily weight gain, survival rate, and parameters water quality (pH, temperature, dissolved oxygen and water discharge). Daily average weight observations are carried out once a week. By providing different feeds, FCR is higher and pellet feed is superior to maggot and pellet combination feed. Pellet feeds produce FCR 2.8 and maggot and pellet combination feeds produce 3.79. With the loss of using maggot mixed feed IDR 15.709.111. Based on these results maggot feed experiments given did not provide a better effect than giving full pellet feed.Keywords: Experiment, red tilapia, different feeding, maggot, FCR, Financial Analysis.